Strategi Lokasi dalam Manajemen Operasional sebagai Penentu Daya Saing Perusahaan - Sinarwaty Sinarwaty; Rina Hasmanah; Yeyen Arisanti; Yuki Aglesia Zahrani Suhadi; Samsul Samsul (Jurnal Ilmiah Ekonomi dan Manajemen Indonesia, 2026)
Location decisions are a strategic aspect of operational management that significantly impacts cost efficiency and revenue growth. This study aims to analyze the concept of location strategy, the factors influencing it, and the methods used to determine optimal locations. The approach used was a qualitative study using a literature review of various academic sources related to operational management. The results show that location strategy is influenced not only by economic factors such as labor and transportation costs, but also by non-economic factors such as political stability, social conditions, and technological developments. Furthermore, there are differences in approach between the manufacturing sector, which focuses on cost efficiency, and the service sector, which places greater emphasis on customer proximity. Therefore, selecting the right location can be a source of sustainable competitive advantage for a company.